Лікувальний масаж та самомасаж при гонартрозі - Андрійчук, Ольга Ярославівна; Andriіchuk, Olga Ya. (Харківська державна академія фізичної культури, 2011)
Подано історичні аспекти становлення масажу, внесок учених у його розвиток. Розглядаються питання як загального впливу лікувального масажу на організм людини, так і локальних ефектів при остеоартрозі колінних суглобів у залежності від застосованих прийомів масажу. Проаналізовано вплив лікувального масажу та самомасажу на об’єктивні (амплітуда рухів у суглобах, сила м'язів) і суб’єктивні зміни у хворих на гонартроз основної та контрольної груп, залежно від рентгенологічної стадії захворювання. Наведено приклади схем і прийомів лікувального масажу та самомасажу, які рекомендується включати в програму реабілітації хворих на гонартроз. This article deals with the historical aspects of establishing the massage, the contribution of scientists into the development of massage. The problems of general influence of the therapeutic massage upon the human organism and the problems of the local effects by osteoarthrosis of knee joints depending on the massage receives are studied. Here is analyzed the influence of therapeutic massage and self-massage upon the objective and subjective changes by persons sick with gonarthrosis in the main and control groups, depending on roentgenological stage of illness. Are given the examples of diagrams and receives of the therapeutic massage and self-massage, which are recommended to be included into the rehabilitation of persons sick with gonarthrosis.
Therapeutic massage and self-massage by gonarthrosis
Keywords: масаж; самомасаж; гонартроз; a massage; a self-massage; gonarthrosis